2023
DOI: 10.1001/jamasurg.2022.5299
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Care Utilization Among Children and Adolescents With a Firearm Injury

Abstract: ImportanceFirearm injuries are a leading cause of morbidity and mortality among US children and adolescents. Despite evidence demonstrating mental health sequelae for children and adolescents who have experienced a firearm injury, little is known about mental health care utilization after a firearm injury.ObjectiveTo evaluate mental health care utilization in the 12 months after a firearm injury among Medicaid-insured and commercially insured children and adolescents compared with propensity score–matched cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Previous retrospective studies have identified increased anxiety, depression, and posttraumatic stress disorders in firearminjured youth 1 year postinjury. [5][6][7] Our study adds to the existing body of literature, demonstrating that deleterious effects are pervasive beyond 1 year. Our findings point to a need for multicenter prospective research with set time points and diagnostic interviews.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Previous retrospective studies have identified increased anxiety, depression, and posttraumatic stress disorders in firearminjured youth 1 year postinjury. [5][6][7] Our study adds to the existing body of literature, demonstrating that deleterious effects are pervasive beyond 1 year. Our findings point to a need for multicenter prospective research with set time points and diagnostic interviews.…”
Section: Discussionmentioning
confidence: 74%
“…4 Pediatric studies using administrative data have shown associations between nonfatal firearm injuries and increased mental health diagnoses, substance-related disorders, and stress-related disorders in the year following injury. 5,6 In addition, firearm-injured youth have greater health care encounters, chronic conditions, and expenditures than matched controls. 7 These studies do not capture youth who did not seek or could not access healthcare, and their retrospective design prevents a more nuanced understanding of patient needs and outcomes.…”
mentioning
confidence: 99%
“…In a recent propensity score-matched analysis comparing youth who had or had not experienced nonfatal firearm injuries, children suffering from firearm injury had a 1.23 times greater risk of utilizing psychotherapy and 1.40 times greater risk of utilizing substance abuse treatment than those without firearm injury. Finally, Black children and adolescents were 1.64 times more likely to utilize mental health care compared with their White counterparts who also experienced firearm injury 14. These illuminating statistics emphasize the importance of the continued development of programs and access to provide mental health care services for our youth in this critical time after their injury.…”
mentioning
confidence: 97%
“…Finally, Black children and adolescents were 1.64 times more likely to utilize mental health care compared with their White counterparts who also experienced firearm injury. 14 These illuminating statistics emphasize the importance of the continued development of programs and access to provide mental health care services for our youth in this critical time after their injury. Early intervention programs and timely follow-up after their index hospitalization may help mitigate the ongoing effects of these injuries on the mental health of youth, trauma recidivism, and potential future criminal justice involvement.…”
mentioning
confidence: 99%
“…The far-reaching, adverse outcomes of firearm-related injuries have been described in the literature, including poor mental health sequelae . In this issue of JAMA Surgery , Oddo and colleagues identified that insured children and adolescents, aged 0 to 17 years, in the US who experienced a nonfatal firearm-related injury were 1.40 times more likely to utilize mental health services in the 12 months following their injury compared with uninjured youths. Among those injured, Black youths were 1.64 times more likely to utilize these services than were White youths.…”
mentioning
confidence: 99%